2020
DOI: 10.1007/s40195-020-01143-8
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Process Parameters on Defects, Melt Pool Shape, Microstructure, and Tensile Behavior of 316L Stainless Steel Produced by Selective Laser Melting

Abstract: Previous studies have revealed that laser power and energy density are significant factors affecting the quality of parts manufactured by selective laser melting (SLM). The normalized equivalent density E 0 * and dimensionless laser power q*, which can be regarded as a progress on the understanding of the corresponding dimensional quantities, are adopted in this study to examine the defects, melt pool shape, and primary dendrite spacing of the SLM-manufactured 316L stainless steel, because it reflects the comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…In this study, it was decided that the test would be carried out using an energy density of between 40 and 120 J/mm 3 after combining the test equipment with the research results of many scholars [ 15 , 21 ]. The energy density was, in turn, determined by the laser power, scanning speed, powder layer thickness, and scanning spacing, so this study decided to choose a laser power of 100 W–160 W, a scanning spacing of 0.06–0.10 mm, a scanning speed of 500–700 mm/s, and a powder layer thickness of 0.04 mm for the construction of porous skeletal scaffolds, for each factor in the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, it was decided that the test would be carried out using an energy density of between 40 and 120 J/mm 3 after combining the test equipment with the research results of many scholars [ 15 , 21 ]. The energy density was, in turn, determined by the laser power, scanning speed, powder layer thickness, and scanning spacing, so this study decided to choose a laser power of 100 W–160 W, a scanning spacing of 0.06–0.10 mm, a scanning speed of 500–700 mm/s, and a powder layer thickness of 0.04 mm for the construction of porous skeletal scaffolds, for each factor in the study.…”
Section: Methodsmentioning
confidence: 99%
“…Ma et al [ 14 ] concluded that higher scanning speeds can be used to obtain uniform and fine microstructures during the forming process due to the faster solidification rate. Jiang et al [ 15 ] and Anil et al [ 16 ] investigated the effect of energy density on the density and defects of SLM-formed parts and found that the use of suitable energy density can result in formed parts with excellent properties. Yadollahi et al [ 17 ] found that the construction process parameters play a decisive role in thermal cycling during the forming process, thus affecting the tissue structure and, hence, the mechanical strength under static and cyclic loading.…”
Section: Introductionmentioning
confidence: 99%
“…The elastic modulus of stainless steel, titanium and titanium alloy is much higher than that of human bone, and it is easy to a produce "stress shielding" effect after implantation; this will affect the normal development of bone tissue near the implantation material [14]. Therefore, as a bone implant material, it is necessary to further improve the biological activity of stainless steel material to promote bone tissue regeneration [15][16][17]. Porous scaffolds also have the advantages of good penetration, adjustable pore size and porosity, and a similar elastic modulus to natural bone tissue, which can effectively prevent the generation of the stress shielding effect [16].…”
Section: Introductionmentioning
confidence: 99%
“…Note that 420 martensitic stainless steel has also been of significant interest in SLM, since its properties are suitable for specific applications, due to its high strength and corrosion resistance [ 18 ]. Consequently, many studies have been published concerning the microstructure, mechanical properties, and roughness of these stainless steels, produced by SLM ([ 19 , 20 , 21 ] −316L, [ 22 , 23 , 24 ]−630, [ 25 , 26 , 27 ]−420). SS 440C is also a martensitic stainless steel, but has high carbon content; it is used in applications where high hardness and corrosion resistance are necessary, such as bearings, knives and automotive parts [ 28 ].…”
Section: Introductionmentioning
confidence: 99%